Lipid droplet-associated hydrolase (LDAH) knockdown enhances TAG hydrolysis and promotes ovarian cancer progression and chemoresistance - Bhawna Deswal; Sameera Nallanthighal; Elahe Nikpayam; Zenab Minhas; Antoni Paul; Young-Hwa Goo; Dong-Joo Cheon (Oncogenesis)
Abstract Lipid droplet-associated hydrolase (LDAH) is a lipid hydrolase abundantly expressed in adipose and ovarian tissues and macrophages. However, LDAH’s functions in ovarian cancer are largely unknown. Analysis of publicly available patient datasets showed decreased LDAH expression in advanced stages of ovarian cancer, and low LDAH levels were associated with poor survival outcomes in ovarian cancer patients. Consistently, knockdown (KD) of LDAH in human ovarian cancer cell lines increased tumor cell proliferation but decreased endoplasmic reticulum (ER) stress and apoptosis upon cisplatin treatment. In addition, compared to scrambled control, LDAH KD ovarian cancer cells showed smaller lipid droplets (LDs), decreased triacylglycerol (TAG) content, and increased expression of adipose triglyceride lipase (ATGL), carnitine palmitoyltransferase 1 A (CPT1A), and phospho-NF-kB. Our xenograft studies also showed increased tumor growth, increased ATGL expression, and decreased apoptosis after cisplatin treatment in LDAH KD tumors. ATGL overexpression increased cisplatin resistance and expression of CPT1A and phospho-NF-kB, whereas treatment of LDAH KD cells with an ATGL inhibitor attenuated the phenotype. Lastly, we observed that high ATGL levels were associated with shorter survival in ovarian cancer patients. Collectively, our results suggest that ovarian cancer cells downregulate LDAH expression, leading to enhanced ATGL-mediated TAG hydrolysis and increased tumor growth and chemoresistance.